A Case Report on the Ayurvedic Management of Diabetic Peripheral Neuropathy (International Journal of Ayurveda and Pharma Research, 2024)
Diabetic neuropathy is one of the most common microvascular complications of diabetes mellitus. It has a significant impact in lowering quality of life (QOL) of diabetic patients. Currently, there is no effective management rather than tight blood sugar control. Hence an effective management for diabetic peripheral neuropathy (DPN) has to be deduced. A 41‑year‑old female patient, who was a known case of diabetes mellitus presenting with the symptoms of diabetic peripheral neuropathy was treated with a combination of Ayurvedic internal as well as external therapies, considering the treatment protocol of Prameha upadrava and Vatarakta chikitsa. The symptoms were assessed before and after treatment using the Toronto Clinical Scoring System. Significant improvement was seen in all the scores after the treatment. This case elicited that DPN can be successfully managed by Ayurvedic treatment.